Pengaruh Employee Engagement terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Mediasi - Abadi, Ahmad Fairuz (Jurnal Ilmu Manajemen, 2024)
PT Angkasa Pura I Juanda International Airport Surabaya Branch is a company that deals with airport management. This company carries out business in airport management, in this case, financing airline rentals, cargo, retail, hotels, and other non-aeronautical revenues. This research aims to test and analyze the influence of employee engagement on employee performance with job satisfaction as a mediating variable for PT Angkasa Pura I Juanda International Airport Branch Office, Surabaya employees. This research is causality research with a quantitative approach. The sampling technique uses non-probability sampling with purposive sampling type. Researchers determined the sample with specific considerations with 87 respondents at PT Angkasa Pura I Juanda International Airport Branch Office, Surabaya. The statistical analysis used in this research is Partial Least Square (PLS) with the help of smart pls 3.2.9 software. The results of this research explain that employee engagement has a positive and significant effect on employee performance, employee engagement has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant impact on employee performance, job satisfaction can mediate the relationship between employee engagement and employee performance. Thus, the managerial implication of this research is that organizations must create a more productive work environment, motivate employees to provide maximum contribution, and improve overall organizational performance.